A Analisis Standarisasi Laboratorium Biologi dalam Mendukung Implementasi Kurikulum Merdeka di MAS Islamic Center Sumatera Utara: Manajemen Laboratorium Biologi - Basyusyi, Aisya (Manajer Pendididikan, 2023)
This research was conducted to determine the standardization of the MAS Islamic Center North Sumatra biology laboratory in supporting the implementation of the independent curriculum. This research is descriptive research using a qualitative approach. The subjects targeted for this research were the head of the laboratory, laboratory managers, biology study teachers, students and biology laboratory infrastructure at the MAS Islamic Center, North Sumatra. Data collection techniques use observation sheets, questionnaires, interview guides and documentation. The results of research on the standardization of the carrying capacity of biological laboratory infrastructure have an average of 87.5% with a very good classification, the standardization of the carrying capacity of facilities has an average percentage of 90.15% with a very good classification, the standardization of laboratory personnel has a percentage of 66.66% in the good category, standardization of management Biology laboratories based on the competencies and sub-competencies possessed by the head of the biology laboratory have a percentage of 85.16%, which is included in the very good classification. The implementation of the independent learning curriculum based on learning principles and assessment principles has good criteria with a percentage of 72.6%. Overall, the MAS Islamic Center North Sumatra biology laboratory has good category standards, the laboratory management is future-oriented by digitizing information so that the MAS Islamic Center North